WASTE POLLUTION AND POLLUTION PREVENTION IN TANJUNG PRIOK PORT WITH GREEN PORT PROGRAM - Romanda Annas Amrullah; Y.B Kusumawardhana; H.I Arsantyo; Gusharianto; M.A Praugusta (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2023)
For environmentally friendly ports in the future, there is a concept called green port where the concept aims to balance economical and ecological port operations. In this study, it aims to determine the impact of pollution and waste generated from the operational activities of Tanjung Priok Port and to find out the efforts carried out by the port to overcome the impact. The research method used by researchers is qualitative by explaining a comprehensive and complex condition that has been observed and understood by directing an in-depth description of the description of a condition which is related to the implementation of the green port concept at Tanjung Priok Port. The data collection technique used is a literature study with a sample of secondary data sources so that the data needed is obtained. Port activities produce pollutants that can harm ecosystems and public health. Therefore, the concept of green port is applied as a solution to prevent pollution with its program called Blue Solution and Port Waste Management System